2002
DOI: 10.1111/1468-5957.00470
|View full text |Cite
|
Sign up to set email alerts
|

Time Varying Market Leverage, the Market Risk Premium and the Cost of Capital

Abstract: This paper shows that, when as usual the market portfolio is proxied by a share portfolio, then the conventional Ibbotson (1999) estimator of the market risk premium violates Miller-Modigliani (1958 and 1963) propositions II and III. A new estimator of the market risk premium is proposed which is free of these defects. In addition, across the range of market leverages experienced in the US in the period 1952-1997, it generates estimates of the market risk premium that differ from those generated by the Ibbotso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(25 citation statements)
references
References 11 publications
0
25
0
Order By: Relevance
“…His suggestion to minimise biases is to base forecast of the equity premium on the real equity return combined with the current inflation expectation. Examples of other work in the area include Merton (1980), who addresses time variation in volatility, and Lally (2002), who addresses time variation in market leverage.…”
Section: 1 R E L E V a N C Ementioning
confidence: 99%
See 1 more Smart Citation
“…His suggestion to minimise biases is to base forecast of the equity premium on the real equity return combined with the current inflation expectation. Examples of other work in the area include Merton (1980), who addresses time variation in volatility, and Lally (2002), who addresses time variation in market leverage.…”
Section: 1 R E L E V a N C Ementioning
confidence: 99%
“…Like the other capital market developments discussed above, the risk spreading resulting from this greater participation suggests that both the total expected return and the equity risk premium might be reduced but, again, the increase is primarily for small investors who do not own a large proportion of the market. Nonetheless, Siegel (1999) suggests that declining transaction costs and increased 48 The composition of future market investments also matter for the returns, for example Lally (2002) also showed that variability of market risk premium depends on the market leverage, providing that the market portfolio is proxied by a portfolio of only equities rather than equities and corporate debt. 49 For example, prior to 1975, brokerage commission on trading individual stocks was set by the New York Stock Exchange, and were substantially higher than they are today (Siegel 1999).…”
mentioning
confidence: 99%
“…Titman and Wessels, 1988;Rajan and Zingales, 1995;Booth, Aivazian, Demiguc-Kunt and Maksimovic, 2001;Lally, 2002), and testing the various well-known theories of capital structure (Frank and Goyal, 2003;Flannery andRangan, 2006, Dang, 2010). Recent studies have attempted to examine the leverage -return relation (Dimitrov and Jain, 2008;Penman et al 2007;Korteweg, 2009;George and Huang, 2009;Muradoglu and Sivaprasad, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Time-varying approaches associate the MRP with some timevarying market factors. Two such approaches are the Merton (1980) method and the Lally (2002) method. (1980) investigates the relationship between the MRP and market risk.…”
Section: Time-varying Approachesmentioning
confidence: 99%
“…Although previous studies have shown evidence of a positive relationship between the MRP and market variance, the form of the relationship remains unclear. Lally (2002) develops a time-varying MRP estimator, which overcomes some problems with the Merton estimator. The Lally method is based on the work of Miller (1958, 1963), whose proposition II specifies the relationship between a company's cost of equity and its leverage.…”
Section: Introductionmentioning
confidence: 99%